2017
DOI: 10.1016/j.cnc.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Using Complementary and Alternative Medicine to Treat Pain and Agitation in Dementia

Abstract: SYNOPSIS The risk of pain in adults with dementia worsens with advancing age. Painful comorbidities may be under-assessed and inadequately treated in adults with dementia. Receiving treatment in critical care settings may indicate greater occurrences of pain, and an increased prevalence of complications. Pain may also exacerbate behavioral and psychological symptoms of dementia (BPSD), such as agitation and stress. Complementary and alternative medicine (CAM) therapies may alleviate pain and incidences of BPSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 47 publications
2
8
0
1
Order By: Relevance
“…In their overview on the potentially beneficial effects of touch for patients treated in an intensive care unit, Harris et al suggest that interpersonal touch is most effective when provided by a relative in a lightly moving way (in contrast to static touch) and that dimmed light might increase the calming effects. These conclusions are in line with research that light massage and touch can improve psychobiological stress levels and decrease pain in older patients with dementia ( 150 ) and patients with pain due to cancer ( 151 ). A touch therapy program in autistic children has been suggested to improve parent–child communication ( 152 ).…”
Section: Conclusion and Clinical Implicationssupporting
confidence: 88%
“…In their overview on the potentially beneficial effects of touch for patients treated in an intensive care unit, Harris et al suggest that interpersonal touch is most effective when provided by a relative in a lightly moving way (in contrast to static touch) and that dimmed light might increase the calming effects. These conclusions are in line with research that light massage and touch can improve psychobiological stress levels and decrease pain in older patients with dementia ( 150 ) and patients with pain due to cancer ( 151 ). A touch therapy program in autistic children has been suggested to improve parent–child communication ( 152 ).…”
Section: Conclusion and Clinical Implicationssupporting
confidence: 88%
“…from this meta-analysis concur with a recent review involving seven quantitative studies using complementary and alternative medicine (CAM) for residents with dementia living in LTC(Anderson et al, 2017). While results from three of the included studies indicated a reduction in pain in people with dementia, it is important to note that only CAM therapies assessed in RCTs were included and the risk of bias and quality of the evidence was unclear.…”
supporting
confidence: 72%
“…However, a systematic review of randomized controlled trials (RCTs) can give more reliable conclusions and avoid possible confounding factors. In addition, previous reviews have only focused on older adults from a specific setting, such as community (Park & Hughes, 2012) or nursing homes (Anderson, Deng, Anthony, Atalla, & Monroe, 2017;Knopp-Sihota et al, 2016;Tederko et al, 2014), which also limits the generalization of the results to a larger population.…”
mentioning
confidence: 99%
“…Another study found evidence for the effectiveness of massage and human interaction, but not for aromatherapy. 59 Also, a relatively small study found significant effects on pain of the PARO robot seal in a population with dementia. 60 …”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%